PERSEPSI PETANI TERHADAP KINERJA PENYULUH PERTANIAN PADI SAWAH DI DESA LANGGOMEA KECAMATAN UEPAI KABUPATEN KONAWE - Dwik Winiasih; Awaluddin Hamzah; Salahuddin Salahuddin; La Ode Kimon (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The objective of this study is to ascertain the perceptions of farmers regarding the performance of agricultural extension workers in paddy rice cultivation in Langgomea Village, Uepai Subdistrict, Konawe Regency, and to examine the relationship between these perceptions and the performance of the workers. The population under investigation in this study consisted of all wet-rice farmers in Langgomea Village. The research sample was selected using the simple random sampling method. The sample size was determined using the Slovin formula, with an error rate of 10%, resulting in a sample size of 52 respondents. This research employs a quantitative data approach. The data were collected via survey, interview, and recording methods with the use of media in the form of questionnaires or other pertinent documentation. This research employs a two-dimensional approach, with the variables of interest being the farmers' perceptions and the performance of agricultural extension workers. The data were processed in two stages or ways: first, using the class interval formula; and second, using the Spearman rank correlation formula. The findings indicate that the perceptions of wet-rice farmers in Langgomea Village, Uepai Subdistrict, Konawe Regency are predominantly positive, as evidenced by their observations, views, and opinions. The performance of agricultural extension workers in Langgomea Village is generally classified as "good," as evidenced by the implementation and impact of the results of the actions of agricultural extension workers at all stages of extension activities, including the planning, implementation, evaluation, and reporting stages. The results demonstrated a significant and positive correlation between farmers' perceptions and the performance of agricultural extension workers in Langgomea Village. Consequently, an improvement in farmers' perceptions of the performance of agricultural extension workers was associated with an enhancement in the performance of agricultural extension workers, and vice versa.